2021
DOI: 10.1080/19439962.2021.1949414
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of factors that influence interstate highway crash severity in Alabama

Abstract: This paper identifies factors that influence the severity of interstate crash outcomes and how they vary depending on the location and manner of collision. Four separate injury severity models were developed to explore the differences and similarities in crash factors between single-and multi-vehicle crashes that occurred in rural and urban areas of the state. Random parameters multinomial logit with heterogeneity in means and variances modeling approach was used to account for unobserved heterogeneity in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Separate mixed multinomial logit injury severity models were estimated for rural and urban motorcycle crashes in Ghana. Like previous crash injury severity studies [28,46,61], during model estimation, variables were included in the specification if they had t-statistics corresponding to the 90% confidence interval on a two-tailed ttest. e random parameters, however, were included if their standard deviations had t-statistics corresponding to the 90% confidence interval.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Separate mixed multinomial logit injury severity models were estimated for rural and urban motorcycle crashes in Ghana. Like previous crash injury severity studies [28,46,61], during model estimation, variables were included in the specification if they had t-statistics corresponding to the 90% confidence interval on a two-tailed ttest. e random parameters, however, were included if their standard deviations had t-statistics corresponding to the 90% confidence interval.…”
Section: Resultsmentioning
confidence: 99%
“…[8] used cross-sectional observations and chi-square tests to investigate the prevalence of helmet use among motorcycle riders and pillion riders in Ghana. Due to the classification of crash severity into discrete outcomes, discrete outcome models, ordered (probit and logit models) and unordered (such as the multinomial logit model) models, have been used to analyze crash severity (see [15,17,27,28,[44][45][46] for injury severity methodology reviews). For instance, Ref.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon the onset of the COVID-19 pandemic, various states across the United States (U.S.) issued stay-at-home orders. The unprecedented orders in turn caused a tremendous reduction in vehicle trips, and consequently the volume of traffic on roads; at the same time, roadway fatality rates increased across the country ( Doucette et al, 2021 , Stiles et al, 2021 , Adanu et al, 2021 , Dong et al, 2022 ). For instance, in Connecticut, despite a 43% reduction in Vehicle Miles Traveled (VMT), the rate of fatal single vehicle crashes increased by 4.1 times in the early stages of the pandemic ( Doucette et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Speeding is a contributing factor in many fatal and serious injury crashes ( Cooper, 1997 , Elvik, 2005 , Abegaz et al, 2014 , Adanu et al, 2021 , Wang and Cicchino, 2023 ). Researchers found that several factors impact speeding, including but not limited to roadway geometry and functional class ( Afghari et al, 2018 , Eluru et al, 2013 ), posted speed limit ( Yokoo and Levinson, 2019 ), time of day, time of week and holidays ( Jun, 2010 , Heydari et al, 2020 ), light conditions ( De Bellis et al, 2018 ), vehicle classification ( Afghari et al, 2018 ), weather conditions ( Kurte et al, 2019 ), enforcement ( Hauer et al, 1982 , Tay, 2005 ), and driver psychology or perceived risk ( Tucker and Marsh, 2021 ).…”
Section: Introductionmentioning
confidence: 99%